PENGARUH SUKROSA TERHADAP KARAKTERISTIK FISIKOKIMIA DAN SENSORIS MANISAN KERING PAPRIKA MERAH (Capsicum annuum var grossum) - Gabriela Sampelani Joseph; Lana Lalujan; Maria F. Sumual (COCOS, 2017)
ABSTRACTSweets are processed food with high sugar level so that can be stored in a relatively long period of time. The purpose of this research was to determine the effect of sucrose concentration on the physicochemical characteristics and to evaluate panelist preferences level of sweetened dried red paprica. The research was arranged in Completely Randomized Design (CRD), with sucrose concentration as treatments. The results showed that the water content of sweetened dried red paprica was ranged from 18.67 to 24.00%. The highest water content was in treatment A1 with 30% sucrose concentration, while the lowest water content was in treatment A4 ( 60% sucrose concentration). The sucrose concentrations were ranged between 40.06 to 67.89% where the highest concentration of sucrose was in treatment A4 (60% sucrose concentration) while the lowest sucrose content was in treatment A1 (30% sucrose concentration). The vitamin C content were ranged from 127.07 to 141.35 mg / 100gr. The texture of sweetened dried red paprica analyzed with penetrometer were ranged between 55.00 to 78.33 mm / g / sec. The Sensory analysis showed that A3 (50% sucrose concentration) was the most preferred sweetened dried red paprica based on its taste, aroma and texture; while A4 ( 60% sucrose concentration) was the most preferred one based on its colour.Keywords : sweetened dried red paprica, physicochemical and sensory properties.